Differential utility of teacher and parent-teacher combined information in the assessment of attention deficit/hyperactivity disorder symptoms - Rosales, Alexandra Garcia; Vitoratou, Silia; Faraone, Stephen V.; Rudaizky, Daniel; Banaschewski, Tobias; Asherson, Philip; Sonuga-Barke, Edmund; Buitelaar, Jan; Oades, Robert D.; Rothenberger, Aribert; Steinhausen, Hans-Christoph; Taylor, Eric; et al. (European child & adolescent psychiatry, 2021)
Consistent research findings indicate that parents and teachers observe genuinely different Attention Deficit/Hyperactivity Disorder (ADHD) behaviours in their respective settings.
Published online: 3 April 2020
Gesehen am 10.06.2021